Análisis de las herramientas Open Source “Clif y Gatling”, para pruebas de fiabilidad y rendimiento en aplicaciones en entorno web. - Villalva Rodríguez, Wilson Darío (2023)
The development of this case study begins with a search on the internet for the Open Source tools Clif and Gatling, the same ones that allow the evaluation of reliability and/or performance metrics, these tools were selected since they are the ones that have the most use. , the existing documentation, characteristics and for its easy handling when running in a web application. The main objective of this case study is to evaluate Open Source tools to carry out reliability and performance tests of web applications. This case is focused to a certain extent for small and medium developers, who cannot access quality evaluation tools with a proprietary license, therefore, this case study aims to demonstrate that there are Open Source tools that work properly and that is within everyone's reach. In order to achieve the objective of this case study, a process is carried out that is made up of several phases: literary review, strategy, mention of methods to generate data and data analysis. The results obtained in a first search are ten basic tools, later it is filtered under certain parameters that reduces the list of tools to two. Finally, after carrying out the literary analysis of the tools under test, satisfactory operation can be verified. The Open Source tools that are mentioned in this case study evaluate the performance of applications in a web environment, they are a good alternative to proprietary software, they perform adequately. However, it should be clarified that at a much higher level of demand it would not work well.